ANALISIS KESULITAN GURU DALAM MENGAJARKAN PEMBELAJARAN MATEMATIKA DI KELAS V SDN 040515 TIGAJUMPA - Morhelini, Ovi; Novi Tari Simbolon; Yosefo Gule (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the difficulties faced by teachers in teaching mathematics in Grade V at SDN 040515 Tigajumpa. The research employed a descriptive design using mixmethod approaches, with data collection techniques consisting of questionnaires, interviews, and observations. The questionnaire was administered to 22 students to obtain an overview of their perceptions of the learning process, while interviews were conducted with the classroom teacher to explore in depth the obstacles encountered. Observations were carried out to obtain factual data regarding the interactions between the teacher and students during the implementation of classroom learning activities. The data were analyzed through data reduction, data display, and conclusion drawing. The results of this study indicate that teachers’ difficulties arise from the interaction of internal and external factors. Internal factors include classroom management, the implementation of student-centered learning, the use of instructional media and information and communication technology, the utilization of learning resources, and the implementation of assessment and feedback that have not been optimal. External factors include students’ low understanding of abstract material, differences in cognitive abilities, limited learning facilities, and a lack of support from the students’ family environment. The interaction of these factors results in the dominance of lecture, question-and-answer, and discussion methods, as well as low student participation, leading to less optimal mathematics learning quality. Therefore, improving the effectiveness of mathematics learning requires strengthening teachers’ competencies and fostering sustainable and synergistic support from various related stakeholders .